Proceedings of the Seventh IEEE International Conference on Computer Vision 1999
DOI: 10.1109/iccv.1999.791221
|View full text |Cite
|
Sign up to set email alerts
|

Posture estimation using structure and motion models

Abstract: Sensing of human motion is very important for humancomputer interactive applications such as virtual reality, gesture recognition, and communication. A vision system is suitable for human-computer interaction since this involves passive sensing and the system can estimate the motion of the user without any discomfort for the user. In this paper, we propose an algorithm for fast posture estimation of the user from an image sequence by using the position information of the hands and head. Our algorithm is founde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Wren and Pentland [145] generalized the concept of knowing the motion beforehand by suggesting that various behavior models may be used to improve the pose estimation. An example of this was also published by Iwai et al [65] where six different motion models are used.…”
Section: Indirect Model Usementioning
confidence: 98%
See 1 more Smart Citation
“…Wren and Pentland [145] generalized the concept of knowing the motion beforehand by suggesting that various behavior models may be used to improve the pose estimation. An example of this was also published by Iwai et al [65] where six different motion models are used.…”
Section: Indirect Model Usementioning
confidence: 98%
“…A good example is Chroma-keying where a person appears in front of a one-color, usually blue, screen wearing nonblue clothes. By thresholding, the person can easily be separated from the background [32,65]. The opposite approach, where the subject wears one color, usually dark, clothes against a different background is also very popular [12].…”
Section: Spatial Datamentioning
confidence: 99%
“…A variety of works in the model based human motion tracking have employed the kinematic chain [82,83,84,85,86,87,88,89,90,91]. Bregler et al [94] demonstrated a comprehensive visual motion estimation technique using the kinematic chain in a complex video sequence, as depicted in Figure 9.…”
Section: Fuzzy Qualitative Kinematicsmentioning
confidence: 99%
“…In the model based human motion tracking, the human body models such as the stick figures, 2D and 3D motion description models are adopted to model the complex, non-rigid structure of the human body [82,83,84,85,86,87,88,89,90,91]. Readers can refer to [20,21,24,92] for the detailed reviews.…”
Section: Model Based Trackingmentioning
confidence: 99%
See 1 more Smart Citation